Loss of muscle strength, mass (sarcopenia), and quality (specific force) and its relationship with functional limitation and physical disability: The concord health and ageing in men project - Hairi, N.N.; Cumming, R.G.; Naganathan, V.; Handelsman, D.J.; Le Couteur, D.G.; Creasey, H.; Waite, L.M.; Seibel, M.J.; Sambrook, P.N. (Wiley, 2010)
OBJECTIVES: To determine the association between loss of muscle strength, mass, and quality and functional limitation and physical disability in older men. DESIGN: Cross-sectional study of older men participating in the Concord Health and Ageing in Men Project (CHAMP). SETTING: Elderly men living in a defined geographical region in Sydney, Australia. PARTICIPANTS: One thousand seven hundred five community-dwelling men aged 70 and older who participated in the baseline assessments of CHAMP. MEASUREMENTS: Upper and lower extremity strength were measured using dynamometers for grip and quadriceps strength. Appendicular skeletal lean mass was assessed using dual X-ray absorptiometry. Muscle quality was defined as the ratio of strength to mass in upper and lower extremities. For each parameter, subjects in the lowest 20% of the distribution were defined as below normal. Functional limitation was assessed according to self-report and objective lower extremity performance measures. Physical disability was measured according to self-report questionnaire. RESULTS: After adjusting for important confounders, the prevalence ratio (PR) for poor quadriceps strength and self-reported functional limitation was 1.91 (95% confidence interval (CI) 51.10-2.40); for performance-based functional limitation the PR was 1.81 (95% CI = 1.45-2.24). The adjusted PR for poor grip strength and physical disability in instrumental activities of daily living (IADLs) was 1.37 (95% CI = 1.20-1.56). The adjusted PR for low skeletal lean mass (adjusted for fat mass) and physical disability in basic activities of daily living was 2.08 (95% CI = 1.37-3.15). For muscle quality, the PR for lower extremity specific force and functional limitation and physical disability was stronger than upper extremity specific force. CONCLUSION: Muscle strength is the single best measure of age-related muscle change and is associated with physical disability in IADLs and functional limitation. J Am Geriatr Soc 58:2055-2062, 2010.